If you care about social equality, you want a big state: Home, work, care and social egalitarianism. Issue 2 (September 2016) - McTernan, Emily; O'Neill, Martin; Schemmel, Christian; Schuppert, Fabian
Abstract : Justified scepticism about distant bureaucracies and transactional politics mutated into a wholesale retreat from the state on the left – but to create a just and egalitarian society, sayEmily McTernan, Martin O'Neill, Christian Schemmel andFabian Schuppert, we need a powerful, democratic 'big state'.